Corelation of Spiritual Well-Being and Stress Level in College Students: A Correlational Study - Muhammad Ari Arfianto; Shabrina Naulal Haqqiyah; Sri Widowati; Muhammad Rosyidul Ibad (Universitas Muhammadiyah Yogyakarta, 2023)
Background: Students often experience stress with varying intensity. Spiritual well-being is considered to have a role in controlling student stress levels. But there are many students who experience stress even though they already have good spiritual well being.Objective: This study aims to explore the correlation between spiritual well-being and stress levels in college students.Methods: This a cross-sectional l study involved 104 students. The sample was selected using an accidental sampling technique. The independent variable of this study was the students' level of spiritual well-being, while the dependent variable was the level of student stress. Data collection uses the Spiritual Well Being Scale Questionnaire and Hassless Assessment Scale for Students in College questionnaires which have been tested for validity and reliability. This research’s results were analyzed using the SPSS application with the Spearman Rho test. Most of the respondents had spiritual welfare in the high category, namely 82.7%. Most of the stress levels experienced by students were at a mild stress level (63.5%).Results: The study found a significant correlation between spiritual well-being and stress level among collge student (p = 0.000 ) with a correlation coefficient of -0.392.Conclusion: This study indicates that there is a significant relationship between spiritual well-being and stress levels in college students, with a weak correlation level and a negative correlation direction, this means that students who have high spiritual well-being have a lower probability of stress.